Making your own retrograde carrier - Chai, W.L.; Ngeow, Wei Cheong (1999)
One of the problems faced by manufacturers is the difficulty in constructing a robust and reliable, angled applicator tip. This can be overcome by handmaking your own retrograde carrier. The applicator tip may be bent to about 50 degrees and, if a kink occurs while bending the tip, it can be replaced easily by a new modified needle. Because the wire used is flexible, it can adapt to the bend without a problem. Narrower carriers can also be made using a 20-G needle, perhaps more suitable for retrograde fillings of molar apices. Because the carrier is designed to be used once only, the problems of it being difficult to load and liable to blockages should not arise.